Safety culture of Petronas ICT staff in Menara Exxonmobil / Razif Mohammed Shahreza - Razif , Mohammed Shahreza (2019)
The oil & gas sector has been well documented as one of the riskiest careers to have as well as the main contributors to man-made disasters. Major accident hazards in the industry worldwide i.e. Explosion, Fire have prompt a more proactive measures from all parties since casualties are not just limited to people but the environment, asset and reputation. A study of culture maturity in PETRONAS-ICT was conducted with the main objectives of this study were to identify the level of safety culture for PETRONAS-ICT employees in Menara Exxonmobil, to determine the possible factors that can affect the employees maturity level on safety culture, and to propose measures to achieve a generative safety culture amongst staff. A total of fifty five (55) employees took part in this study. A questionnaire was used to analyse the level of safety culture understanding based on employees’ personal experience within the organisation. Likert scale was utilized as part of the questionnaire and to determine the effectiveness of the eight (8) HSEMS elements and their key areas. Interview sessions were also conducted to further gage on why several respondents believe that the level of safety culture is still at the Pathological and Reactive level.The significant findings from the study indicated that majority of PETRONAS-ICT staff are already at the Proactive level. Nevertheless, PETRONAS-ICT aspires their employees to reach the next level and achieve the Generative safety culture. Therefore, it is proposed that the organization to continuously improve HSE performances across the group as to provide a world class HSE experiences among the employees thus elevating the safety culture maturity level, beliefs and improve the productivity and actions of the employees. Ultimately, this will reduce the number of workplace accidents.